Real estate market structure: Industrial organization perspectives - Abdullah, Muhammad Ridhuan Bos (Universiti Utara Malaysia, 2015)
Existing studies of housing markets assume that property developers is a homogenous, perfectly competitive industry.It concentrates on advanced economies and the impacts of market conditions, regulatory constraints, production characteristics, institutional structure and land supply.Motivated by these circumstances and fewer literature on concentration studies in Malaysia we try to bridging the gap.This paper utilized 5-digit firm level industry data of the Malaysian Standard Industrial Classification (MSIC, 2008) on the average size of property developer establishments and market concentration to test the appropriateness of this paradigm.Our concentration ratio (CR4) results show Malaysian real estate services are considered as competitive market.